Health care providers' attitudes and counseling behaviors related to obesity - Marjanna Smith; Christine Gallagher; Deanne Weber; William H. Dietz (Wiley, 2023)
Abstract Background Obesity affects over 42% of the U.S. adult population, yet it remains undertreated. Many healthcare providers are biased in their perceptions and attitudes regarding obesity management and lack knowledge about how to treat it. Methods The authors analyzed the results of the 2021 DocStyles survey to examine primary care providers' treatment and perceptions of obesity. The sample consisted of primary care physicians and nurse practitioners/physician assistants. Questions assessed healthcare providers' attitudes and counseling behaviors related to obesity, including referrals, use of medical therapy, barriers to care, and perceived risk factors for obesity. Results 1168 primary care providers who treat obesity participated in the survey. About half of the providers reported referring patients for obesity treatment. Almost two‐thirds of providers had prescribed anti‐obesity medications in the last 12 months. Those who did not prescribe anti‐obesity medications reported a lack of familiarity with the medications or concerns about safety. Over three‐quarters of providers indicated at least one barrier to treating obesity. Over half of the providers reported that poverty and food insecurity contributed significantly to the high prevalence of obesity in communities of color. Conclusion Increased familiarity with anti‐obesity medications may improve treatment. Reasons for patients' low priority accorded to obesity care remain the focus of future research.